2011
DOI: 10.1021/jp2058113
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism and Roles of Arg197 and Thr183 in the Staphylococcus aureus Sortase A Enzyme

Abstract: The sortase A enzyme, which catalyzes the peptidoglycan cell wall anchoring reaction of LPXTG surface proteins, has been proposed to be a universal target for therapeutic agents against Gram-positive bacteria. The catalytic mechanism of the Staphylococcus aureus sortase A enzyme has been systematically studied using molecular dynamics simulations, ONIOM(DFT:MM) calculations, and QM/MM charge deletion analysis. The catalytic roles of Arg197 and Thr183 were analyzed. Our calculations show that Arg197 has several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…Conformations of the SrtA-LPAT complex in which the threonine side chain of the sorting signal forms interactions with the active site arginine were obtained without major rearrangement of the structure of the enzyme. Interestingly, a previous MD study based on the SrtA-LPAT* NMR structure reports that the active site arginine residue functions only to position the sorting signal substrate by hydrogen bonding to its backbone carbonyl atoms at positions P2 and P4 (25). Our work is compatible with this conclusion but suggests that this stabilizing interaction will only occur when the P1 Thr samples the out position that is presumably not catalytically active.…”
Section: Discussionsupporting
confidence: 86%
“…Conformations of the SrtA-LPAT complex in which the threonine side chain of the sorting signal forms interactions with the active site arginine were obtained without major rearrangement of the structure of the enzyme. Interestingly, a previous MD study based on the SrtA-LPAT* NMR structure reports that the active site arginine residue functions only to position the sorting signal substrate by hydrogen bonding to its backbone carbonyl atoms at positions P2 and P4 (25). Our work is compatible with this conclusion but suggests that this stabilizing interaction will only occur when the P1 Thr samples the out position that is presumably not catalytically active.…”
Section: Discussionsupporting
confidence: 86%
“…Comparative simulations with LPAT, APAT, and LAAT substrates demonstrated that contacts between the leucine side chain and SaSrtA contribute to stabilize the β 6/ β 7 loop, whereas the kink that is induced by the proline appears to be essential for recognition. In another study, Tian and Eriksson performed simulations in which His120 and Cys184 were in their zwitterionic and neutral forms (Tian & Eriksson, 2011). Their results showed that Arg197 adopts distinct conformations based upon the charged state of the protein, which helps to stabilize the catalytically active form.…”
Section: Computational Studiesmentioning
confidence: 99%
“…This process is presumably assisted by the conserved active site histidine residue, which may act as a general acid to protonate the amino leaving group. Beyond stabilizing the oxyanion intermediate, the side chain of the active site arginine residue may orient the substrate in the active site by forming a hydrogen bond to the backbone carbonyl atom in the P2 residue (Chan et al, 2015; Suree et al, 2009; Tian & Eriksson, 2011). In the next step of the reaction, a secondary substrate bearing an amine group enters the active site and is presumably deprotonated by the active site histidine residue to facilitate its nucleophilic attack on the thioacyl bond (Fig.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…The authors investigated the interactions between the diarylacrylonitrile derivative and the SrtA enzyme (PDB:1IJA) using molecular modelling. Although DMMA does not form an interaction with Cys 184, which is crucial for transpeptidation activity, the nitrile group forms a hydrogen bond with the catalytic residue Arg 197 [40], and the phenyl rings form strong lipophilic interactions with amino acids in the large hydrophobic binding pocket of the SrtA active site. A subsequent study examined the inhibitory effects of DMMA in vivo providing the first data of SrtA inhibitor use in animals [41].…”
Section: Synthetic Small Moleculesmentioning
confidence: 99%